Problems faced by the first-year students at Thanhhoa College of Culture and Arts in developing vocabulary for speaking in different subject areas - Nguyen, Thi Ha My (ĐHNN, 2017)
The importance of vocabulary is undeniable in language learning. Therefore, understanding the difficulties faced by students in learning vocabulary is apparently necessary to gain effective learning. This minor thesis was carried out with an attempt to inv (...)